Optimization of Income Tax at North Karawang North KPP - Liya Megawati; Novian Ekawaty (Jurnal Manajemen dan Bisnis Kreatif, 2020)
This study aims to determine how the optimization of income tax revenue carried out by KPP Pratama Karawang Utara, Karawang Regency. To answer this problem, researchers used a descriptive qualitative approach. The object of this research is North Karawang Pratama KPP Regency. The data of this study were obtained from secondary data and interviews conducted at North Karawang North KPP employees. The results of this study indicate that the implementation of the optimization of income tax receipts at North Karawang North Tax Office is not optimal, because there are still obstacles in its implementation. Keyword: income tax, North Karawang North Tax Office